Tasks of a municipality in a field of municipal waste management fee - Bartosz Namieciński (Prawo Budżetowe Państwa i Samorządu)
Municipalities are entrusted with numerous tasks related to a municipal waste management. However, the implementation of these tasks is not possible without ensuring an adequate level of financial resources. These funds come from the municipal waste management fee, which is an obligatory public tribute. In this regard, the financial tasks of the municipality consist of the obligation to determine the shape of the aforementioned fee. This fee is a complex normative construct which contains solutions that, in addition to achieving fiscal goals, also encourage individuals to take actions to protect the environment. Adoption of solutions that gratify the behavior of taxpayers of the municipal waste management fee, which at the same time achieve environmental protection purposes, can contribute to reducing the amount of a waste generated by municipalities, and thus - to reduce the cost of operating this system and to increasing the effectiveness of an implementation of municipal tasks, especially those of a financial nature. The purpose of the conducted research is to verify the financial tasks of municipalities in the field of the municipal waste management and to systematize them. Aiming to verify theoretical considerations with practical content, the study was carried out in this regard in the area of the city of Szczecin and municipalities of the Policki District. The article was developed using the dogmatic-legal research method and the empirical-analytical method.